Dexamethasone for the treatment of established postoperative nausea and vomiting: A randomised dose finding trial. Issue 6 (16th June 2022) - Czarnetzki, Christoph; Albrecht, Eric; Desmeules, Jules; Kern, Christian; Corpataux, Jean-Baptiste; Gander, Sylvain; van Kuijk, Sander M.J.; Tramèr, Martin R.
Abstract : BACKGROUND: Dexamethasone is widely used for the prevention of postoperative nausea and vomiting (PONV) but little is known about its efficacy for the treatment of established PONV. OBJECTIVE: To test the antiemetic efficacy of intravenous dexamethasone for the treatment of established PONV in adults undergoing surgery under general anaesthesia and to determine whether there is dose-responsiveness. DESIGN: The DexPonv trial is a multicentre, placebo-controlled, randomised, double-blind, dose-finding study. Inclusion of patients was between September 2012 and November 2017. Follow-up for PONV symptoms was for 24 h. Thirty days postoperatively, patients were contacted by study nurses for any information on postoperative bleeding and infection. SETTING: Four public hospitals in Switzerland. PATIENTS: A total of 803 adults scheduled for elective surgery without any antiemetic prophylaxis signed the consent form; 714 were included. Among those, 319 had PONV and 281 patients were eventually randomised (intention to treat population and safety set). The per protocol set consisted of 260 patients. INTERVENTIONS: Patients with PONV symptoms (including retching) were randomised to a single intravenous dose of dexamethasone 3, 6 or 12 mg or matching placebo. MAIN OUTCOME MEASURES: The primary endpoint was the absence of further nausea or vomiting (including retching), within 24 h after administration of the study drug. RESULTS: Dexamethasone was ineffective during the first 24 h, whatever the dosage, compared to placebo, even when the model was adjusted for known risk factors ( P = 0.170). There were no differences in the time to treatment failure or the quality of sleep during the first night. There was a positive correlation between the dose of dexamethasone and blood glucose concentrations ( P < 0.001), but not with bleeding risk, wound infections or other adverse effects. CONCLUSION: This randomised trial failed to show anti-emetic efficacy of any of the tested intravenous regimens of dexamethasone for the treatment of established PONV in adults undergoing surgery under general anaesthesia. TRIAL REGISTRATION: clinicaltrials.gov (NCT01975727).